LTBK-05. Outcomes of Infants and Young Children with Newly Diagnosed Localized (M0) SHH Medulloblastoma Treated on The NEXT Consortium "Head Start" 4 Protocol. (13th June 2022) - Dhall, Girish; Stanek, Joseph; Blue, Megan; Patel, Parth; Thomas, Diana; Pierson, Christopher; Tamrazi, Benita; Mahadeo, Kris M; Fleming, Jessica; Bell, Erica; Miller, Katherine; Grischow, Olivia; et al.
Abstract: Advances in RNA and DNA profiling have identified four core molecular subgroups of medulloblastoma of prognostic significance: Sonic Hedgehog (SHH) subtype, WNT subtype, Group 3, and Group 4. Infants and young children with SHH medulloblastoma have demonstrated a favorable outcome in clinical trials utilizing either high-dose chemotherapy ("Head Start") or a combination of intravenous and intraventricular methotrexate (HIT-SKK). Two recently conducted clinical trials (COG ACNS1221 and St. Jude – SJYC07) failed to demonstrate similar survival advantage with conventional dose chemotherapy and without intraventricular methotrexate. "Head Start" 4 (HS 4) is a prospective randomized clinical trial that tailors treatment based on medulloblastoma molecular subgroups and response to induction chemotherapy to compare the efficacy of one versus versus three (tandem) cycles of myeloablative therapy. Eligibility includes newly diagnosed children less than six years of age with localized medulloblastoma. Eligible patients with SHH medulloblastoma were considered "low-risk" and non-randomly assigned to receive three cycles of induction chemotherapy (vincristine, cisplatin, cyclophosphamide, etoposide, and high-dose methotrexate) followed by consolidation with single cycle of myeloablative chemotherapy (thiotepa, carboplatin, etoposide) and autologous hematopoietic progenitor cell rescue. Patients with less than a complete response after three induction cycles received two additional cycles prior to consolidation therapy. Only children between 6 -10 years old, or those with confirmed residual tumor post-consolidation, were meant to receive irradiation after consolidation. Twenty-eight children with localized SHH medulloblastoma were enrolled on the trial with a median age of 2.1 years (range: 0.3-5.9 years). Median follow-up for this cohort is 29.6 months (range: 7.0-58.6 months). The estimated 3-year event-free (EFS) and overall survival (OS) is 96% (CI: 89-100%) and 100%, respectively. The estimated 3-year EFS for SHH subtype 1 and 2 patients is 100% and 95%, respectively (p=0.65). None of the M0 SHH medulloblastoma patients received irradiation.